2017
DOI: 10.22341/jacs.on.00401p338
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Substitution of Corn Meal from the Concentrate of Plus-Complete Feed with Fermented Cocoa Pod on Growth of the Young Male Bali Cattle

Abstract: Abstract:The study aimed to evaluate the effects of substitution of corn meal from concentrate of plus-complete feed (PCF) with fermented cocoa pod (FCP) on growth of the young male Bali Cattle. Fifteen young male Bali Cattles were randomly assigned into five groups for the substitutions of corn meal from the PCF by FCP treatments i.e 0, 25, 50, 75 and 100 % which each group was replicated by three subgroups. The pods were fermented with yeast Aspergillus niger that had been activated by combinations of sugar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The higher the dose of herbicide given, the more emphasis is placed on it and can reduce selectivity. In line with this statement, Hartati et al (2017) reported that the lower the dose used, the more active ingredients contained and unable to control weed growth properly.…”
Section: Total Weed Dry Weightmentioning
confidence: 69%
“…The higher the dose of herbicide given, the more emphasis is placed on it and can reduce selectivity. In line with this statement, Hartati et al (2017) reported that the lower the dose used, the more active ingredients contained and unable to control weed growth properly.…”
Section: Total Weed Dry Weightmentioning
confidence: 69%
“…which is able to influence increased VFA production. Increased VFA production can indicate the ease with which nutrients in feed, especially carbohydrates and proteins, are degraded by rumen microbes, so that VFA production in the rumen can be used as a measure of feed fermentability which is closely related to rumen microbial activity and population [8]. [9] added that the NH3 concentration is determined by the level of feed protein, the degree of degradability and the length of time the feed is in the rumen can determine the ammonia concentration.…”
Section: Effect Of Treatment On the Concentration Of Vfa Nh3 And Ph O...mentioning
confidence: 99%